The Influence of the Realistic Mathematic Education Model Assisted by Learning Videos on Students' Learning Activities and Outcomes in Elementary School - Wildatul Husna; Zuwirna; Alwen Bentri; Darmansyah (Postgraduate, University of Mataram, 2025)
This study aims to investigate the effect of the video-assisted Realistic Mathematics Education (RME) model on the learning activities and outcomes of elementary school students. The research employed a quasi-experimental design involving fourth-grade students from two different schools. Data were collected using a questionnaire to measure student learning activities and a test to assess mathematics learning outcomes. The data were then analyzed using appropriate quantitative statistical procedures to evaluate differences and relationships between the variables studied. The findings show that the implementation of the RME model supported by video learning had a significant effect on both learning activities and student achievement in mathematics. Students who participated in video-assisted RME learning demonstrated higher levels of engagement during classroom activities compared to their peers in the control group. In addition, their mathematics test scores were consistently better, indicating an improvement in conceptual understanding and problem-solving abilities. The analysis also revealed a strong and positive relationship between students’ active involvement in learning and their academic performance. These results highlight the potential of combining the RME approach with digital media to foster more interactive and effective learning experiences. The study concludes that the integration of video resources within the RME model can serve as an innovative strategy to enhance student activity and achievement in elementary mathematics education.